EFFECT OF QUIZIZZ TOWARDS THE ELEVENTH-GRADE ENGLISH STUDENTS’ READING COMPREHENSION IN MOBILE LEARNING CONTEXT - N.W.I. Priyanti; M.H. Santosa; K.S. Dewi (Universitas Pendidikan Ganesha, 2019)
The research’s aim was to investigate the effect of Quizizz towards the eleventh grade students’ English study. A quasi-experimental utilizing a post-test only control group was employed for data gathering. Research’s population included eleventh-grade students in SMA Negeri 4 Singaraja. The sample was 37 students of XI IPS 1 as the experimental group who were treated through Quizizz and 36 students of XI IPS 2 as the control group who were treated through conventional teaching strategy. The method of data collection employed multiple choice test. The result showed scores of experimental group (M=83.08, p value=0.018) and control group (M=80.77, p value= 0.018). Mean score of experimental group was higher than the control group (83.08>80.77) and the p value was 0.018 or less than 0.05. The small effect was supported by result specification of reading comprehension text dominated by literal recognition aspects. In conclusion, Quizizz affected students reading comprehension.